Geographic distribution, conservation status and lectotypification of Pedersenia weberbaueri (Suess.) Holub (Amaranthaceae), an endemic and highly threatened shrub from the Marañón valley of Peru - Gonzáles, Paúl (2022)
The present study analyses the geographical distribution, conservation status, and nomenclature of Peruvian endemic Pedersenia weberbaueri. The species distribution was modelled using MaxEnt based on occurrence data and bioclimatic variables. The conservation status of the species was assessed against the categories and criteria of the IUCN Red List, and nomenclatural and typification issues were resolved. The potential distribution map of P. weberbaueri shows that the species is restricted to the seasonally dry tropical forests of the Marañón valley within a narrow latitudinal, longitudinal, and elevational range. Consequently, we propose to categorise the species as Endangered (EN) and provide the necessary information for its inclusion in the IUCN Red List. Finally, we resolve nomenclatural issues and designate a lectotype. The results contribute to the biological knowledge of P. weberbaueri and support subsequent conservation management plans.